Case report: Pleural effusion during tyrosine-kinase inhibitor treatment in chronic myeloid leukemia: Not only a dasatinib-related adverse event - Pasquale, Raffaella; Bucelli, Cristina; Bellani, Valentina; Zappa, Manuela; Iurlo, Alessandra; Cattaneo, Daniele (Frontiers in Oncology, 2022)
The spectrum of TKI-related adverse events (AEs) is variable. Pleural effusion (PE) is a frequent AE attributable to dasatinib treatment, while it is only rarely associated with nilotinib. The pathogenetic mechanism leading to PE during nilotinib therapy is still unknown and its management has not yet been defined. To the best of our knowledge, only a limited number of similar case reports have already been reported in the literature so far. Here, we describe the case of a 41-year-old CML patient who developed PE during first-line nilotinib, successfully treated with steroids and nilotinib permanent discontinuation. We highlight the differences among our patient and the others, proposing therapeutic strategies to solve this rare but still possible AE, of which physicians should be aware.